2017
DOI: 10.1002/mrd.22848
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 induces cumulus cell apoptosis through inhibition of epidermal growth factor receptor‐mediated PI3K/AKT signaling pathways during in vitro maturation of pig oocytes

Abstract: Gangliosides are components of the mammalian plasma membrane that help regulate receptor signaling. Ganglioside GM3, for example, plays an important role in initiating apoptosis in cancer cells; however, physiological roles for GM3 in normal processes, such as during pig oocyte maturation, are not clear. The aim of this study was to investigate the functional link between GM3 and cellular apoptosis in porcine cumulus-oocyte-complexes (COCs) during in vitro maturation. Our results indicated that denuded oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Similarly, GM3 inhibits c-fos and c-jun expression, and thus consequently the inhibition of c-fos and c-jun by GM3 is consistent with the inhibition of MAP kinase activity by GM3 [84]. Additionally, Park et al [36] showed that in porcine cumulus-oocyte complexes (COCs), exogenous GM3 inhibits meiotic maturation and restricts the expansion of cumulus cells during in vitro meiotic maturation through EGFR-mediated PI3K/AKT signaling pathways and initiates apoptosis (Figure 3). GM3 also works and shows increased apoptosis in human colon cancer [85] and murine bladder cancer [34].…”
Section: Gangliosides On Oocytes and Preimplantation Embryossupporting
confidence: 56%
See 2 more Smart Citations
“…Similarly, GM3 inhibits c-fos and c-jun expression, and thus consequently the inhibition of c-fos and c-jun by GM3 is consistent with the inhibition of MAP kinase activity by GM3 [84]. Additionally, Park et al [36] showed that in porcine cumulus-oocyte complexes (COCs), exogenous GM3 inhibits meiotic maturation and restricts the expansion of cumulus cells during in vitro meiotic maturation through EGFR-mediated PI3K/AKT signaling pathways and initiates apoptosis (Figure 3). GM3 also works and shows increased apoptosis in human colon cancer [85] and murine bladder cancer [34].…”
Section: Gangliosides On Oocytes and Preimplantation Embryossupporting
confidence: 56%
“…Continuous mitochondrial regulation releases pro-apoptotic proteins such as cytochrome c into the cytoplasm causing caspase cascades processed by apoptosis, the programed cell death [52].The most compelling evidence shows that GM3 treatment decreases phosphorylated EGFR levels and regulates down-stream EGFR activation in cumulus-oocyte complexes COCs. Consequently, GM3 exposure reduces EGFR-delivered PI3K/AKT signaling for proliferation during in vitro maturation of porcine COCs [36].…”
Section: Gangliosides On Oocytes and Preimplantation Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, GSLs can modify cell signaling in response to specific stimuli. Examples for this are the interactions of GSLs with EGFR (Hofman et al, 2008;Park et al, 2017;Coskun et al, 2011) and the notch ligand delta-like 1 (Dll1) (Heuss et al, 2013). Here, their signalingand as a consequence, the downstream transcriptional responsesare influenced by their interaction with GSLs at the PM.…”
Section: The Regulatory Circuits Of Gsl Expressionmentioning
confidence: 99%
“…In a previous report, the PI3K/AKT signaling pathway was associated with the developmental competence of bovine oocytes [ 12 ]. Additionally, supplementation with certain proteins (e.g., hormones and gangliosides) in IVM medium affects the developmental capacity via modulation of the PI3K/AKT signaling pathway [ 13 , 14 ]. Therefore, it has been suggested that the AKT activity in oocytes differs between class I and class II COCs and that it might be regulated to increase maturation competence and subsequent early embryonic development.…”
Section: Introductionmentioning
confidence: 99%